Dexmedetomidine Sedation in Magnetic Resonance–Guided Focused Ultrasound Thalamotomy: A Case Series of 3 Patients. Issue 11 (3rd June 2019) - Fusco, Pierfrancesco; De Sanctis, Francesca; Di Carlo, Stefano; Petrucci, Emiliano; Scimia, Paolo; Masciocchi, Carlo; Colantonio, Laura Brigitta; Marinangeli, Franco
Abstract : Magnetic resonance–guided focused ultrasound thalamotomy is an innovative minimally invasive treatment for medication-resistant tremor in patients with essential tremor and Parkinson disease. Sedation with common hypnotic agents is discouraged because the patient's cooperation is required during the procedure, and these drugs interact with the patient's tremor, interfering with the results of intraprocedural neurological evaluations. Dexmedetomidine may be the best choice for sedation during magnetic resonance–guided focused ultrasound thalamotomy, which can be prolonged and poorly tolerated by the awake patient. We report the first use of dexmedetomidine for sedation in magnetic resonance–guided focused ultrasound thalamotomy in 3 patients: none of them experienced relevant hemodynamic changes or apnea.